PENGEMBANGAN POTENSI REMAJA DALAM ORGANISASI HIMPUNAN PELAJAR MAHASISWA INDONESIA PAREPARE (HIPMI PARE) - Ramang, Afriyani; Latif, M. Ali; Alamsyah, Muhammad Nur; Febriansa, Febriansa (JAPPA: Jurnal Andragogi Pedagogi dan Pemberdayaan Masyarakat, 2025)
This research aims to find out what programmes of work exist in the HIPMI PARE organization affect the development potential. This research uses a qualitative approach to the type of case study research. The subjects of this study are members of HIPMI PARE, while the object of this research is the organization HIPMY PARE. The collection is done by the method of interviews, observations and documentation. The techniques used in data analysis are information collection, data reduction, data presentation and conclusion drawing. Triangulation is used to explain the validity of data using source triangulation and triangulation techniques. Through the HIPMI PARE work programme our potential can be developed through various activities where we are motivated, dig potential, awaken awareness of the potential that we have, and give the opportunity to play a role to its widest. By developing self-potential, we can become more self-reliant, creative individuals, and have the ability to make a positive contribution to society. Therefore, it is important for organizations of both students' and youth organizations to provide the means for us young people to develop their own potential.Keywords: Potential Teenagers, Organization